Effects of U-Mo Irradiation Creep Performance on the Thermo-Mechanical Coupling Behavior in U-Mo/Al Monolithic Fuel Assemblies - Mao, Xiaoxiao; Jian, Xiaobin; Zhang, Jingyu; Yan, Feng; Ding, Shurong; Huo, Yongzhong; Wang, Haoyu; Zhang, Lin; Li, Yuanming (Frontiers in Energy Research, 2021)
To obtain the optimized fuel performance, the effects of U-Mo irradiation creep rate coefficient on the thermo-mechanical behavior of a fuel assembly are investigated. In this study, three cases of creep rate coefficient are considered. The distribution and evolution results of temperature, displacement, stress/strain and fuel foil micro-structure are analyzed. The simulation results indicate that with the increase of creep rate coefficient 1) the temperature field in the fuel assembly changes slightly; 2) the maximum out-of-plane displacements in the side plates decrease slightly; the maximum out-of-plane displacements in the fuel plates adjacent to the outside Al plates rise distinctly, induced by the enhanced bending deformation contributions; 3) the peak values of the first principal stresses and skeleton normal stresses in the fuel foils are reduced, while the through-thickness creep strains are enlarged; 4) with an increase of fuel creep rate coefficient from 500 × 10−22 mm3/(fission MPa) to 2,000 × 10−22 mm3/(fission·MPa), the maximum Von Mises stress in the fuel cladding decreases by ∼24% on the 308th day. This work is helpful for advanced fabrication and optimization design of U-Mo/Al fuel assemblies.